DESCRIPTION OF STRESS ON EMPLOYEES AT MUHAMMADIYAH UNIVERSITY JAKARTA AFTER THE COVID-19 PANDEMIC - Dewi, Yuwanita Sinta (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
They were adapting new habits after the COVID-19 pandemic in the form of implementing work-from-home (WFH) creates work pressure that can disrupt the psychological stability of employees. This study aims to determine the description of stress on employees. This research is a quantitative descriptive study with the population being employees at the University of Muhammadiyah Jakarta, with a sample of 87 respondents. Data were collected using an online form using the HARS (Hamilton Anxiety Rating Scale) questionnaire. The data was then analyzed descriptively. The results showed that of employees who experienced stress, 9.4% were female, 23.4% were at the age of 36 years, 18.4% had a bachelor's degree, 16.7% were married, and 16.7% had years of work >9 years. The stress levels experienced by employees should pay attention to the work environment by providing supporting facilities, and related parties can notice the dual role shared by employees.